Social Resources are Associated With Higher Fertility Intentions in Contemporary Finland - Artamonova, Alyona (Bundesinstitut für Bevölkerungsforschung, 2025)
Lower childbearing intentions can stem from a lack of social resources. However, not only actual but also perceived social support might signal that parents and parents-to-be will not be alone after having a child. Using register and GGS-Finland data from 2021-22, we investigate how emotional and instrumental support received from parents and other social network members, as well as a person’s subjective feeling that their social network is sufficient (measured as the absence of loneliness), are associated with fertility intentions. Logistic regression models reveal that receiving instrumental support ‒ especially financial support ‒ from parents and other relatives (but not non-kin) is associated with higher childbearing intentions. Not feeling lonely is also associated with higher childbearing intentions, particularly among individuals aged 26-30 years. Gender and partnership status nuance these associations. We conclude that social resources ‒ indicated by both perceived and received support ‒ shape childbearing intentions for those approaching or in prime childbearing age. The lack of perceived social resources among young adults may contribute to relatively low fertility, even in a high-income country with generous family policies such as Finland.